Pratiques langagières, pratiques plurilingues: quelles spécificités? quels outils d’analyse? Regards sur l’opacité du discours - Gajo, Laurent (Travaux neuchâtelois de linguistique, 2003)
This article aims at a better understanding of the characteristics usually linked to plurilingual discourse. Through the analysis of plurilingual and monolingual sequences within school and hospital interactions, the issue is to demonstrate that these characteristics certainly are more obvious and «accountable» in plurilingual interactions, but are not specific to them. A particular attention is paid to the characteristic of discursive «opacity», which is considered as a strategy rather linked to the context definition than to the plurilingual situation.